En beskrivning av hur arbetsterapi kan användas inom missbruksvård : En litteraturöversikt - Bergman, Frida; Leyes Vidèn, Antonia (2016)
The purpose with this study was to give a description of how occupational therapy can be used within addiction treatment. The authors choosed to do a literature review that included both qualitative and quantative studies. Relevant literature were searched in 6 databases that were available via Luleå University Library. In total, 15 articles were included in the result. In the result, four different categories was formed. These categories were: Occupational therapy and the person behind the abuse, The value of the therapeutic relationship, The meaning of occupations to change daily life, and The therapeutic value of the group. The result showed that occupational therapy can be used both when addicts are to stop using substances and when to find new strategies and occupations that are needed to replace the substance abuse occupations and maintain a sober and independent lifestyle. More quantitative research is needed to strengthen the role of occupational therapy and it’s meaning in addiction treatment. More qualitative research is needed to gain understanding for treatment through occupational therapist´s and addict´s experiences. Also, Swedish research is needed to clarify how the occupational therapy work can be formed and a natural part of the addictive treatment within the Swedish context.Keyword: Abuse, addiction treatment, occupational therapy, substance use, value of occupations Validerat; 20160608 (global_studentproject_submitter)